Redang Island In The Eyes Of International Tourist - N Alia Fahada W Ab Rahman; Monizaihasra Mohamed; Farizah Sulong; Mohd Roslan Rosnon; Azreen Jihan Che Mohd Hashim (Human Resource Management Academic Research Society, 2024)
This study investigates Tripadvisor as manifestation of tourist experience. The tourist experience posted on TripAdvisor were analysed to gain insight of the destination experience being expressed. The content was analysed to discover what tourists were communicating about their experience in Redang. Results revealed that major strength of the destinations were its activities, natural resources, and infrastructure while international tourists’ experience with environment is mixed of positive and negative comments. This study demonstrated that TripAdvisor as an established travel reviews are an inexpensive means to collect authentic and spontaneous tourist view. This source also served as an cost-effective ways for destination marketers to understand their service quality and enhance the tourist satisfaction.